Spatial integration of navigation data as efficient method to improve quality of vessel traffic services support - Kravchenko, O.I.; Shcherbina, K.A.; Msallam, E.P.; Vonsovich, M.A. (Radiotekhnika, 2018)
Practical need for the integration of navigation data received by spatially-dispersed network of coast navigation stations of vessels traffic service in coastal regions has been proved. Technical supportability, potential and conceptual peculiarities of the integrated processing implementation of the abovementioned navigation data have been outlined. Perspectives of effective implementation of various well-known conceptual approaches to the development of such systems have been compared and analyzed. The functional scheme of the working automated radio system with a multi radar data processing subsystem has been developed. Its accuracy has been analyzed. The method has been offered and the experimental studies results have been cited to prove the effectiveness of the navigation data integrated processing to support the theoretical expectations. The presented data show that the current integral of the error parameter is considered to have minimal fluctuations, and the standard error shall not exceed the corresponding errors of each of the partial channels.